Development of new flame retardant synergist for polypropylene - Ng, Jing Wen (Nanyang Technological University, 2020)
This report provides detailed documentation of the author’s final year project spanning over the duration of a year. The project is focused on the development of polypropylene (PP) based nanocomposites with good flame-retardant properties. PP is the second most widely used thermoplastic for a variety of applications such as toys and industrial equipment. However, PP is known to be highly flammable and has high self-ignition and decomposition rates, which is a safety hazard in the case of fire. In order to improve the flame retardancy properties of PP, flame-retardant (FR) additives are usually added and mixed with PP. The most widely used FR additives today are halogenated. They are highly effective due to the release of volatile flame inhibitors upon burning, however, they are at the same time toxic to the environment and human health. Therefore, the motivation of this project is to develop new environmentally friendly FR additives to be compounded with PP. In this project, phosphorous and nitrogen-based flame retardants are specifically used in the synthesis together with ammonium polyphosphate (APP-0M). Characterisation tools were used upon completion of the synthesis – energy dispersive x-ray (EDX) analysis with a scanning electron microscope (SEM) to confirm the elements that consist of the FR additives and bonding. Compounding was done to obtain samples to carry out a preliminary flammability test referenced from the UL94 50 W (20 mm) vertical burning test. This study covers 2 synthesis which has proven effectiveness for flame retardancy. However, the effectiveness still requires further optimization and characterisation work before concluding.